How to Document ‐ Ocean Acidification Data. Issue 3 (May 2016) - Jiang, Li‐Qing; Arzayus, Krisa M.; Gattuso, Jean‐Pierre; Garcia, Hernam E.; Chandler, Cynthia; Kozyr, Alex; Yang, Yan; Thomas, Rob; Beck, Brian; Spears, Tobias
Abstract : The number of ocean acidification (OA) studies has increased significantly over the last decade. Most of this was due to studies on biological responses of organisms to OA. The lack of a protocol to document biological response OA data prevents the research community from properly archiving, discovering, accessing, and utilizing this important body of OA data sets. In this e‐Lecture, we present how to document an OA data set by explaining major components of a metadata template, which can be applied to a broad spectrum of OA studies, including those studying the biological responses to OA. The major metadata components include Investigators, Title, Abstract, Temporal coverage, Spatial coverage, Geographic names, Location of organism collection, Platforms, Variable metadata clusters, Publications describing the data set, and Supplementary information. Of these components, Variable metadata clusters (variables and their metadata sub‐elements) are treated as the focal point of the template. In addition to variable name, other metadata elements include the observation type, whether it is an in‐situ observation, manipulation condition, or response variable, biological subject, life stage of the biological subject, etc. Information about how to access the metadata template files is also stated.